Emerging Market Heterogeneity : Insights from Cluster and Taxonomy Analysis - Zhang, Zhongxia (IMF Working Papers; Working Paper ;, 2015)
This paper studies growth patterns in Emerging Market Economies (EMs) from the perspective on clusters and taxonomies. First, it documents developments over the past five decades in EMs and uses a cluster analysis to better understand convergence and the investment-growth nexus. Second, it looks at the performance of EMs since 2000 and develops a taxonomy to classify countries according to their factor endowments as well as their real and financial external linkages. The taxonomy offers insights on growth dynamics pre and post the global financial crisis. Results highlight the high degree of heterogeneity in EMs and the need for more granular and targeted near and long-term policy advice.